Hermite–Hadamard-Type Inequalities for F-Convex Functions via Katugampola Fractional Integral. (8th May 2021) - Set, Erhan; Mumcu, İlker
Abstract : This article is organized as follows: First, definitions, theorems, and other relevant information required to obtain the main results of the article are presented. Second, a new version of the Hermite–Hadamard inequality is proved for the F-convex function class using a fractional integral operator introduced by Katugampola. Finally, new fractional Hermite–Hadamard-type inequalities are given with the help of F-convexity.